Apixaban for the Secondary Prevention of Thrombosis Among Patients With Antiphospholipid Syndrome: Study Rationale and Design (ASTRO-APS). (April 2016) - Woller, Scott C.; Stevens, Scott M.; Kaplan, David A.; Branch, D. Ware; Aston, Valerie T.; Wilson, Emily L.; Gallo, Heather M.; Johnson, Eric G.; Rondina, Matthew T.; Lloyd, James F.; Evans, R. Scott; Elliott, C. Gregory
Background: Antiphospholipid syndrome (APS) is an acquired thrombophilia characterized by thrombosis, pregnancy morbidity, and the presence of characteristic antibodies. Current therapy for patients having APS with a history of thrombosis necessitates anticoagulation with the vitamin K antagonist warfarin, a challenging drug to manage. Apixaban, approved for the treatment and prevention of venous thrombosis with a low rate of bleeding observed, has never been studied among patients with APS. Aims and Methods: We report study rationale and design of Apixaban for the Secondary Prevention of Thrombosis Among Patients With Antiphospholipid Syndrome (ASTRO-APS), a prospective randomized open-label blinded event pilot study that will randomize patients with a clinical diagnosis of APS receiving therapeutic anticoagulation to either adjusted-dose warfarin or apixaban 2.5 mg twice a day. We aim to report our ability to identify, recruit, randomize, and retain patients with APS randomized to apixaban compared with warfarin. We will report clinically important outcomes of thrombosis and bleeding. All clinical outcomes will be adjudicated by a panel blinded to the treatment arm. A unique aspect of this study is the enrollment of patients with an established clinical diagnosis of APS. Also unique is our use of electronic medical record interrogation techniques to identify patients who would likely meet our inclusion criteria and use of an electronic portal for follow-up visit data capture. Conclusion: ASTRO-APS will be the largest prospective study to date comparing a direct oral anticoagulant with warfarin among patients with APS for the secondary prevention of thrombosis. Our inclusion criteria assure that outcomes obtained will be clinically applicable to the routine management of patients with APS receiving indefinite anticoagulation.